Trust management XIII : 13th IFIP WG 11.11 International Conference, IFIPTM 2019, Copenhagen, Denmark, July 17-19, 2019, Proceedings /: 13th IFIP WG 11.11 International Conference, IFIPTM 2019, Copenhagen, Denmark, July 17-19, 2019, Proceedings. (2019) - Unknown
No abstract available